Pengaruh Penggunaan Zeolit dan Serat Agave Sisalana Terhadap Kuat Tekan dengan Metode Self Compacting Concrete (SCC) - Zulkarnain, Fahrizal; Batubara, Amar Azhari (Department of Civil Engineering, Diponegoro University, 2024)
Self Compacting Concrete (SCC) is concrete innovation which does not require vibrations during installation and compaction. SCC concrete can flow freely with its weight and is capable of filling a mold well, ensuring perfect compaction without vibration. In 1988, in order to eliminate or reduce the need for vibration to achieve density and thereby reduce the labor required for concrete placement, SCC was developed in Japan. In this research, the production of SCC was investigated by replacing the fine aggregate in the SCC mixture by 3%, 7% and 11% of zeolite material and by adding 0.005% of agave sisalana fiber of cement weight. The 15/30 cm concrete cylinders were used in 16 samples for compressive strength. It is shown that the values of flowability, filling capacity, and permeability decrease with increasing use of zeolite content based on the results of the research conducted. The results of the compressive strength test show that the variation of 7% zeolite + 0.005% sisalana fiber has the highest value of compressive strength at FAS 0.43, with an average of 38.46 MPa, and the highest value of compressive strength at FAS 0.45, with an average of 37.07 MPa.